Digitalisasi UMKM Perempuan Sebagai Upaya Penguatan Ekonomi Keluarga Dan Komunitas - Siti Hanifah; Moh Bahrudin; Evi Ekawati (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
Digitalization has become a key driver in the transformation of the global economy, including in the development of Micro, Small, and Medium Enterprises (MSMEs). This study aims to analyze the role of digitalization in empowering women-owned MSMEs and strengthening household and community economies. The research employs a qualitative approach using a literature review method by examining various relevant sources from academic journals and scholarly books. The findings indicate that digitalization has a significant positive impact on the performance of women-owned MSMEs, particularly in expanding market access, improving operational efficiency, and enhancing financial inclusion through the use of digital technologies such as e-commerce, social media, and digital financial services. Furthermore, digitalization contributes to increased household income and creates broader economic opportunities at the community level. However, the study also reveals that the implementation of digitalization faces several challenges, including low levels of digital literacy, limited access to technological infrastructure, and socio-cultural barriers that affect women’s participation in the digital economy. These challenges result in a gap between the potential benefits and the actual implementation of digitalization among women entrepreneurs. Therefore, integrated efforts from multiple stakeholders are needed to enhance women’s digital capacity through training programs, improved access to technology, and inclusive policy support. This study contributes to the existing literature on digital-based women’s economic empowerment and provides insights for developing sustainable strategies to strengthen women-owned MSMEs in the digital era.